LEGAL PROTECTION OF INTELLECTUAL PROPERTY AS AN IMPORTANT FACTOR IN THE INNOVATIVE DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN (World Conference on Social Sciences, Law and Public Policy, 2026)
The article examines the legal protection of intellectual property objects as a key factor in the innovative development of the Republic of Uzbekistan. It analyzes the legal foundations for the formation and development of the intellectual property institution within national legislation, including its constitutional, civil, administrative, and criminal law aspects. Special attention is paid to the role of international treaties and Uzbekistan’s participation in the World Intellectual Property Organization in improving the national system of intellectual property protection. The study reviews the regulatory framework governing intellectual property relations, as well as the socio-economic and legal factors determining the necessity of criminal law protection of intellectual property objects. The author concludes that effective legal protection of intellectual property is an essential prerequisite for the development of an innovation-driven economy and the enhancement of the state’s intellectual potential.
Keywords: intellectual property, legal protection, innovative development, Republic of Uzbekistan, international law, WIPO, civil law, criminal law protection, legal regulation, intellectual property objects